Right Pulmonary Cyst in the Child with Central Nervous System Damage: Clinical Case - Tatyana A. Kryuchkova (Вопросы современной педиатрии)
Background. Pulmonary cysts is relatively rare disease for pediatrics and it is 3.5-5.5% of all non-specific lung diseases. There are congenital and acquired pulmonary cysts. Pulmonary cysts in right lung are slightly more common than in the left one. Understanding the nature of cavitary lesion is one of the most difficult problem in pulmonology. Basic diagnostics of cysts is radiological methods.Clinical Case Description. The child (11 y 10 m) was diagnosed with pulmonary cyst in the right lung with local pneumothorax and alongside with congenital developmental brain malformation and symptomatic epilepsy. The first episode of severe acute right-sided pneumonia was diagnosed at the age of 11 y 7 m, he was on hospital stay at place of residence for two weeks. The big cavitary lesion was revealed in right lung. The pulmonary cyst was suspected. One month after the child was hospitalized again in the in intensive care unit with worsening course due to acute respiratory infection. Taking into account big cavitary lesion in right lung he was sent to Moscow for further examination and treatment. The diagnosis of right pulmonary cyst was confirmed. The thoracoscopic lobectomy was performed at the age of 11 y 10 m. The laparoscopic gastrostomy and fundoplication were performed due to gastroesophageal reflux and questionable hiatal hernia one month later. Post-surgery period was without any complications. Spontaneous stool was on the second day, activization of the patient was on the third day. According to check-up X-rays: no diaphragm defects, it is located correctly. The patient was discharged stable to the place of residence for further observation by pediatrician and surgeon.Conclusion. Right pulmonary cyst in the child remained unrecognized for a long time due to mild symptoms. It was revealed only when the child was admitted for the hospital treatment at the place of residence with acute bilateral pneumonia. Timely diagnosis and treatment of such lung pathology are important both for prognosis the disease course and sustaining of patient's quality of life.